2013
DOI: 10.4172/2157-7579.1000140
|View full text |Cite
|
Sign up to set email alerts
|

Liver Abscess in Dromedary Camels (Camelusdromedaries): Oxidative Stress Biomarkers and Proinflammatory Cytokines

Abstract: Background: The characteristic clinical manifestations, oxidative stress markers and proinflammatory Cytokines in liver abscess in camel are poorly defined.Objective: Our objectives were to investigate liver abscess in camel at the slaughter house and to address its effect on blood cellular and biochemical values particularly oxidative stress markers and proinflammatory cytokines.Methods: Thirty-five camels with liver abscesses and 15 healthy camels were included in this study. Complete blood picture, and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Data described in this study provide a reliable biochemical evidence for the generation of circulating oxidative stress as detected by enhanced lipid peroxidation (sMDA and eMDA) and decreased serum levels of the enzymatic (SOD, CAT) and non-enzymatic (GSH) antioxidant markers in dromedary camels suffering UTI. It was reported that MDA levels were increased in a varieties of inflammatory conditions like acute and chronic cystitis in camels ( Abd Ellah, Khamis & Elnisr, 2012 ), UTI in human patients ( Kurutas et al, 2005 ), liver abscess in camels ( El-Deeb & Fouda, 2013 ), mastitis in does ( El-Deeb, 2013 ) pneumonia in calves ( El-Bahr & EL-Deeb, 2013 ). In addition, levels of lipid hydroperoxide were increased in erythrocytes isolated from dairy cows with acute mastitis ( Castillo et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data described in this study provide a reliable biochemical evidence for the generation of circulating oxidative stress as detected by enhanced lipid peroxidation (sMDA and eMDA) and decreased serum levels of the enzymatic (SOD, CAT) and non-enzymatic (GSH) antioxidant markers in dromedary camels suffering UTI. It was reported that MDA levels were increased in a varieties of inflammatory conditions like acute and chronic cystitis in camels ( Abd Ellah, Khamis & Elnisr, 2012 ), UTI in human patients ( Kurutas et al, 2005 ), liver abscess in camels ( El-Deeb & Fouda, 2013 ), mastitis in does ( El-Deeb, 2013 ) pneumonia in calves ( El-Bahr & EL-Deeb, 2013 ). In addition, levels of lipid hydroperoxide were increased in erythrocytes isolated from dairy cows with acute mastitis ( Castillo et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%